The Teaching Media for Mangrove Photosynthesis E-Booklets With a Socioscientific Issue Approach Through PBL Improve Students' Critical Thinking - Fajarianingtyas, Dyah Ayu; Hidayat, Jefri Nur; Herowati, Herowati; Azizah, Lutfiana Fazat (Jurnal Pedagogi dan Pembelajaran, 2023)
The low ability of students' critical thinking is due to the need for more use of media to support the development of students' thinking skills. This study aims to produce SSI e-booklet teaching media and test the effectiveness of PBL in increasing students' critical thinking. This research belongs to the development research type developed using the ADDIE model, with analysis, design, development, implementation, and evaluation stages. The subjects involved in this study were 29 junior high school students. Data collection in the study was carried out using observation, interview, and test methods. The instrument used is in the form of a test in the form of free essay questions. Data analysis used the free sample t-test and the gain score. The research analysis results showed that the validity level of the SSI e-booklet on mangrove photosynthesis was in a very good category. The effectiveness of PBL learning using the SSI e-booklet is very effective. There are differences in students' critical thinking between the control and experimental classes. Based on these results, applying the SSI e-booklet media through PBL has proven effective in improving students' critical thinking skills.